2009
DOI: 10.1159/000236003
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Lavage in Pregnant Women with Seasonal Allergic Rhinitis: A Randomized Study

Abstract: Background: Nasal rinsing appears particularly suitable in the management of pregnant women with seasonal allergic rhinitis since no deleterious effects on the fetus are to be expected. However, to date, no studies have specifically investigated this option. Methods: Pregnant women with seasonal allergic rhinitis were randomized to intranasal lavage with hypertonic saline solution 3 times daily (n = 22) versus no local therapy (n = 23) during a 6-week period corresponding to the pollen season. Patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 39 publications
3
53
0
6
Order By: Relevance
“…The efficacy of BHS is also supported by the significant decrease of the use of antihistamine in 2nd visit. It is in line with Garavello et al [19,27]. Furthermore, we found that the BHS group had better compliance with irrigations than the NSS group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The efficacy of BHS is also supported by the significant decrease of the use of antihistamine in 2nd visit. It is in line with Garavello et al [19,27]. Furthermore, we found that the BHS group had better compliance with irrigations than the NSS group.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in line with previous studies. Garavello et al [19] found that BHS nasal irrigation in AR significantly decreased mean daily score, Subsequently, they reported that hypertonic saline nasal irrigation in pregnant woman with seasonal AR significant improved rhinitis score [27]. However, NSS irrigation was not included in both study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this population, hypertonic irrigation three times daily led to reduced self-reported nasal symptoms, medication use, and objective measurements of nasal patency (115). In addition, rinsers had a markedly reduced need for oral AHs during 5 of the 7 weeks (114).…”
Section: Role Of Nasal Saline Irrigation In the Treatment Of Ar And Narmentioning
confidence: 95%
“…To overcome these problems at least partially, NI has been considered and several studies were planned to evaluate its real efficacy. A systematic review and meta-analysis of the studies published until 2010 [73] selected 10 trials [37,74,75,76,77,78,79,80,81,82], 7 of which were randomized and controlled studies. Three studies included children.…”
Section: Clinical Efficacymentioning
confidence: 99%